SMARCA4-deficient undifferentiated tumor achieved by transbronchial mediastinal cryobiopsy additional to needle aspiration - Zhang, Jing; Zhou, Dong; Fu, Wan-Lei; Guo, Jie-Ru; Cheng, Tian-Le; Jiang, Yun-Qiu; Huang, Zan-Sheng; Herth, Felix; Fan, Ye (Respiration, 2023)
Lung cancer is the leading cause of deaths from malignant neoplasms worldwide, and a satisfactory biopsy that allows for histological and other analyses is critical for its diagnosis. Guidelines have recommended endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) as the reference standard for the staging of lung cancer. However, the relatively limited sample volume retrieved by needle aspiration might restrict the diagnostic capacity of EBUS-TBNA in other uncommon thoracic tumors. Transbronchial mediastinal cryobiopsy is a recently developed sampling strategy for mediastinal lesions, which demonstrates added diagnostic value to conventional needle aspiration. Here, we present a case of thoracic SMARCA4-deficient undifferentiated tumor successfully diagnosed by mediastinal cryobiopsy additional to EBUS-TBNA.